Chlamydia trachomatis: opportunistic screening in primary care. - Tobin, C (2001)
Following the publication of the Chief Medical Officer's report on chlamydial screening, we identified the sexual health of young women as an area for concern. As part of our review we decided to opportunistically search for chlamydial genital infections using a non-invasive technique. Sexually active women under 25 years of age were invited to submit a first void urine sample for polymerase chain reaction analysis. Over the period of a year we found out that 10.9% of sexually active young women tested positive for chlamydia in our practice.